A review of sources, status, and risks of microplastics in the largest semi-enclosed sea of China, the Bohai Sea. (November 2022) - Gu, Xiang; Liu, Shanshan; Li, Yang; Ouyang, Wei; He, Mengchang; Liu, Xitao; Lin, Chunye
Abstract: The largest semi-enclosed sea of China, the Bohai Sea, serves as an important sink of microplastics (MPs) originated from terrestrial and marine sources. This study summarized potential sources and migration pathways of MPs in the Bohai Sea and reviewed the abundance and characteristics of MPs in water, sediments, and organisms. Coastal anthropogenic activities (i.e., plastic production, agricultural activities, and industrial and domestic sewage discharge) and marine origins (i.e., aquaculture, marine litters, and transportation) might accelerate the MPs enrichment in the Bohai Sea. The abundance of MPs ranged from 0.07 to 5200 items/m 3 in the seawater, mainly influenced by the application of different trawl nets/sieves with different sizes (0.005–0.33 mm). Sediments of coastal rivers contained the MPs ranging from 56.7 to 1795 items/kg, significantly higher than that of the Bohai Sea (6.24–461.6 items/kg). Among organisms, the average abundance of MPs was the lowest in zooplanktons (0.03 items/animal), significantly lower than that in invertebrates (1.39 items/animal) and fish (2.12 items/animal), but no biomagnification of MPs was observed. The preliminary risk assessment indicated that seawater in the Liaodong Bay had medium ecological risk of MPs while other bays of the Bohai Sea had minor risks. To make the ecological risk of MPs quantifiable and comparable, future research priorities are recommended to focus on more frequent field surveys, standardization of sampling methods, and establishment of toxicity database of common polymer types of MPs in the Bohai Sea. Graphical abstract: Image 1 Highlights: Sources, abundance, composition, and risks of MPs in the Bohai Sea were reviewed. Significant relationships between trawl size and abundance of MPs were established. Abundance of MPs in sediments was significantly higher in rivers than the sea. Abundance of MPs in zooplankton was significantly lower than secondary consumers. ●The Liaodong Bay was considered to experience a medium ecological risk of MPs.